2011
DOI: 10.1007/s10705-011-9435-3
|View full text |Cite
|
Sign up to set email alerts
|

Selenium fractions in selenate-fertilized field soils of Finland

Abstract: Depending on the soil environment, selenium (Se) can exist as several species differing greatly in bioavailability. Characterization of soil Se reserves is thus necessary in assessing the nutritional supply of this essential element. In low-Se areas, Se fertilization is an option for securing adequate Se nutrition. Fertilization is, however, challenged by the unknown fate of the residual Se. In this study, we aimed to clarify the Se status of selenate-fertilized field soils by fractionating soil Se into five p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Approximately half of the Se fertilizer that has been absorbed by the crop plants is returned with the organic residues into the soil after harvest. The small increase in organic Se pool in our study is in line with earlier results by Yläranta (1985) and Keskinen et al (2011).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Approximately half of the Se fertilizer that has been absorbed by the crop plants is returned with the organic residues into the soil after harvest. The small increase in organic Se pool in our study is in line with earlier results by Yläranta (1985) and Keskinen et al (2011).…”
Section: Discussionsupporting
confidence: 94%
“…In their 25-year followup study with selenate, Eurola et al (2008) found no change in hot-water extractable soil Se concentration). In contrast, long-term (1992 to 2004) selenate application to mineral soil is reported to have elevated the Se concentration in adsorbed, organically associated and recalcitrant (organic Se or metal selenides extracted by NaOCl) fractions by 5, 15 and 9 lg kg -1 , respectively (Keskinen et al 2011). This outcome supports Yläranta's (1985) assumption that residual Se accumulates in soil in an insoluble form.…”
Section: Introductionmentioning
confidence: 96%
“…Whilst the uptake of Se by crops in biofortification studies has been studied extensively, the retention of residual Se in the soil has received limited attention (Keskinen et al 2011). This issue needs to be addressed if Se biofortification is to be implemented on a large scale and over long time periods.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the relatively low annual Se addition (10-20 g ha À1 ) the time frame since the rst application of selenate in biofortication measures (20-30 years) has been too short to allow reliable conclusions about the environmental fate of the remaining 80-95% of the added Se. 72,92,93 In our study, the interval between rst selenate input and detectable changes is considerably shortened due to the large quantity of irrigation induced Se (2.6 to 5.2 kg ha À1 ) and can thus be taken as helpful case study to resolve questions about the biofortication inuenced Se cycling.…”
Section: Implications For Biofortication Measuresmentioning
confidence: 97%